Kewarisan Beda Agama dalam Perspektif Hukum Islam dan Kompilasi Hukum Islam: Analisis Normatif terhadap Putusan Pengadilan di Indonesia - Sawaluddin Siregar; Nursania Dasopang (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the regulation of interfaith inheritance within the framework of Islamic law and the Compilation of Islamic Law (KHI) through a normative analysis of Indonesian court decisions. Islamic inheritance law fundamentally requires religious uniformity between the decedent and heirs, positioning religious difference as a legal impediment to inheritance. The KHI adopts classical Islamic jurisprudence by explicitly stipulating that only Muslim heirs are entitled to inherit from a Muslim decedent. However, judicial practice in Indonesia demonstrates a progressive development, particularly through Supreme Court decisions that introduce wasiat wajibah as an alternative legal mechanism to protect the civil rights of non-Muslim family members. This legal construction does not confer heir status but provides a mandatory bequest as a form of equitable distribution. The coexistence of strict normative rules and judicial discretion reflects an ongoing effort to balance legal certainty, justice, and social realities in pluralistic Indonesian society. The findings indicate that interfaith inheritance law in Indonesia evolves through jurisprudence rather than legislative reform, reinforcing the role of courts in bridging doctrinal rigidity and substantive justice.